Effectiveness of peer‐supervision on pediatric fever illness treatment among registered private drug sellers in East‐Central Uganda: An interrupted time series analysis. Issue 2 (7th May 2021) - Bagonza, Arthur; Kitutu, Freddy Eric; Peterson, Stefan; Mårtensson, Andreas; Mutto, Milton; Awor, Phyllis; Mukanga, David; Wamani, Henry
Abstract: Rationale, aims, and objectives: Appropriate treatment of pediatric fever in rural areas remains a challenge and maybe partly due to inadequate supervision of licensed drug sellers. This study assessed the effectiveness of peer‐supervision among drug sellers on the appropriate treatment of pneumonia symptoms, uncomplicated malaria, and non‐bloody diarrhea among children less than 5 years of age in the intervention (Luuka) and comparison (Buyende) districts, in East‐Central Uganda. Methods: Data on pneumonia symptoms, uncomplicated malaria, and non‐bloody diarrhea among children less than 5 years of age was abstracted from drug shop sick child registers over a 12‐month period; 6 months before and 6 months after the introduction of peer‐supervision. Interrupted time series were applied to determine the effectiveness of the peer‐supervision intervention on the appropriate treatment of pneumonia, uncomplicated malaria, and non‐bloody diarrhea among children less than 5 years of age attending drug shops in East Central Uganda. Results: The proportion of children treated appropriately for pneumonia symptoms was 10.84% ( P  < .05, CI = [1.75, 19.9]) higher, for uncomplicated malaria was 1.46% ( P = .79, CI = [−10.43, 13.36]) higher, and for non‐bloody diarrhea was 4.00% ( P  < .05, CI = [−7.95, −0.13]) lower in the intervention district than the comparison district, respectively. Post‐intervention trend results showed an increase of 1.21% ( P = .008, CI = [0.36, 2.05]) in the proportion appropriately treated for pneumonia symptoms, no difference in appropriate treatment for uncomplicated malaria, and a reduction of 1% ( P  < .06, CI = [−1.95, 0.02]) in the proportion of children appropriately treated for non‐bloody diarrhea, respectively. Conclusions: Peer‐supervision increased the proportion of children less than 5 years of age that received appropriate treatment for pneumonia symptoms but not for uncomplicated malaria and non‐bloody diarrhea. Implementation of community‐level interventions to improve pediatric fever management should consider including peer‐supervision among drug sellers.